Accuracy of Cone-beam Computed Tomography in diagnosing root canal configuration: a literature review - Nisrina, Nur Asmy; Yunus, Barunawaty (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This review article aims to describe the accuracy of cone-beam computed tomography (CBCT) in diagnosing root canal configuration. Review: This study is a literature review consisting of English articles about the accuracy of cone-beam computed tomography in diagnosing root canal configuration, published in 2013 – 2023. The article search databases used were Pubmed and Science Direct with the keyword “(cone-beam computed tomography[MeSH Terms]) AND (configuration, root canal[MeSH Terms]).” The selected articles were screened by checking the publication year, duplicating articles, reading the titles and abstracts, and the entire article's contents. The total search results for articles based on keywords obtained were 205 and only seven were included. In order to successfully perform root canal treatment, thorough knowledge of the root canal configuration is essential. Cone-beam computed tomography (CBCT) can improve our understanding of root canal configuration. The development of CBCT has brought to light the disadvantages of conventional radiography, which include the compression of three-dimensional anatomy, geometric distortion, and anatomical noise. Conclusion: Radiology is essential in treatment planning, disease monitoring, and assessmen t of treatment outcomes. The development of cone-beam computed tomography (CBCT) offers three-dimensional accuracy with a reasonable cost, no geometric distortion and anatomical noise, and the ability to create cross-sectional images, revolutionizing the imaging of dentomaxillofacial structures. This imaging system has been shown to overcome some of the limitations of conventional radiography.